2011
DOI: 10.1007/s00266-011-9793-x
|View full text |Cite
|
Sign up to set email alerts
|

The Blue-Eyes Stereotype: Do Eye Color, Pupil Diameter, and Scleral Color Affect Attractiveness?

Abstract: The data showed that the "blue-eyes stereotype" does exist. People consider blue eyes attractive, but in reality, blue is rated as attractive as other iridal colors. Bright scleral color and large pupils positively affect attractiveness because both features are significantly correlated with youthfulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 24 publications
5
34
0
Order By: Relevance
“…Study 1 loosely replicated the finding by Griindl et al (2012) that the sclera becomes darker and more saturated (i.e., less white) with age, but using a different color space and a larger set of faces. Study 2 extends this work by showing experimentally that sclera coloration is used as a cue for perceiving the age, health, and beauty of the face.…”
Section: Discussionsupporting
confidence: 68%
“…Study 1 loosely replicated the finding by Griindl et al (2012) that the sclera becomes darker and more saturated (i.e., less white) with age, but using a different color space and a larger set of faces. Study 2 extends this work by showing experimentally that sclera coloration is used as a cue for perceiving the age, health, and beauty of the face.…”
Section: Discussionsupporting
confidence: 68%
“…We found that there are declines in facial contrast with age in men as well as women, that were very similar to those found in a previous study with only female faces (Porcheron et al, 2013). With age, red-green and yellow-blue contrast around the eyes decreases in part because the sclera becomes redder and yellower with age (Gründl, Knoll, Eisenmann-Klein, & Prantl, 2012;Russell, Sweda, Porcheron, & Mauger, 2014). We also observed a decrease of the absolute value of red-green lips contrasts in both female and male faces.…”
Section: Discussionsupporting
confidence: 89%
“…For us humans, the eyes are not only sensory organs but, when observed by others, also an extremely important socio-cognitive stimulus. The wealth of information conveyed by the human eyes includes cues of health and age (Russell et al 2014 ; Gründl et al 2012 ), social interest (Kret et al 2014 ), emotional and attentional states (Provine et al 2013 ; Hess and Polt 1960 ) as well as behavioural intent (Adams and Kleck 2005 ) and male dominance (Kleisner et al 2010 ; but see also: Kocnar et al 2012 , who did not confrim the association between eye morphology and male dominance). This informative function is underscored by the uniqueness of the ocular morphology in our species (Kobayashi and Kohshima 1997 ).…”
mentioning
confidence: 99%